Devolution in natural resource management: institutional arrangements and power shifts: a synthesis of case studies from southern Africa - Shackleton, S.; Campbell, Bruce M. (Center for International Forestry Research, 2001)
The study provides a comparative analysis of the devolution and empowerment process in 14 case studies drawn from eight countries in southern Africa. Each case study examined the extent to which policy and legislation devolves significant control over decision making and benefit flows to communities; the legitimacy and power of different community institutions and their relationship with other stakeholders such as local authority structures, NGOs, donor agencies, and the private sector; and lastly the relationship and divisions between different actors and groupings in the community. The impacts of devolution were found to differ considerably among case studies both within and between countries,of the countries from which they derive. The study revealed that while some empowerment schemes appear to be marked success others appear doomed to failure, or if one is more optimistic, have resulted in the development of capacity within certain organisations but are unlikely to result in sustainable systems of natural resource management.In the countries studied, there have been progress towards CBNRM and a more away from the previous, largely unsuccessful, centralised command and control approaches to natural resources management.In some cases the move to community -based management has been more successful in empowering local communities than in others. In most instances there is little evidence, with the possible exception of specific case studies in Nambia and Malawi, to demonstrate that devolved authority has resulted in more sustainable natural resource management. The assumption is that if true community control is in place then sustainable NRM still require attention and further research effort. The study also revealed a range of factors and conditions that may help contribute to the success of CBNRM initiatives and the empowerment of local communities. The chances of CBNRM succeeding appear greater in situations where high value resources are involved, which have the potential to provide communities with an income stream which give incentive to participate and comply with rule and regulation..